Multidisciplinary view on the link of environmental activism with art creation: a case study of recycled (junk) art / Ryunosuke Kikuchi - Ryunosuke, Kikuchi (Faculty of Art and Design, 2023)
It is reported that the world of art needs more social enterprise and the world of social enterprise needs more art. Therefore, a case study of recycled art was carried out in order to investigate how the link between the art movement and the environmental movement has been formed. Recycled art is often considered as a form of environmental activism. However, there is a time lag of about half a century between the initiation of recycled art in the early 20th century and that of environmental activism (e.g. 3R's - reduce, reuse and recycle) in the 1970s. Recycled art is not historically linked with environmental activism, but it is currently and practically linked with environmental activism. The reuse/recycling of waste as an art tool was new and novel for the then progressive artists from the artistic viewpoint. Since there is now increasing concern over environmental issues and measures to address such issues across the world, the reuse/recycling of waste as an art tool is environmentally friendly from the 3R's viewpoint. That is, these two viewpoints are quite different, but the outcome of recycled art fulfills both interests – artistic creativity and waste abatement. Our modern society has a lot of complex problems; therefore, cooperation across different sectors is often required. Recycled art seems to be a thought-provoking example for working together across sectoral boundaries.